GIS in The Humanities: The Spatial Pattern and Distribution of the Voyage of Panglima Awang or Henry The Black (Malay Literature, 2012)
Panglima Awang or Henry The Black or Enrique of Melaka, a man of Malay descent, was on board Ferdinand Magellan's ship when he made his voyage around the world. Panglima Awang was a captive and a slave on board. He was taken to Goa, India and then onward to Portugal. In Portugal, a conflict broke out between the Portugese and Captain Fernado (or Ferdinand Magellan) who, at the instigation of Da Gama, was maliciously accused of siding with some foreigners. Tired of the unwelcome pressure, Captain Fernado made the decision to change his mission and instead sail around the world with Panglima Awang. From Portugal they set sail for Spain. Also on board was Pigafetta who recorded every little detail of the voyage. Besides depicting the events that took place during the voyage of Panglima Awang, this article attempts to integrate geographical information technology into research in the fields of literature and history. This is achieved by identifying the route taken by Panglima Awang as well as his stopover locations, and analysing the spatial pattern and distribution of the voyage.Keywords: Geographical Information System (GIS), Humanities, voyage, Panglima Awang